О языковой ситуации в одном из ареалов юго-восточной части Вильнюсского района - Савич, Н. А. (Kalbotyra, 1990)
The article deals with the present linguistic situation in the Vilnius District, which is very complicated and not quite clear for the people who call themselves Poles, but in every-day communication use one of the Byelorussian dialects. Though being Catholics, as a matter of fact they speak Byelorussian. The author provides a great number of patterns of their language, called “prostaya mova”, and investigates its linguistic geography in Kalveliai, Kena, Pakenė and other villages in the south-eastern part of the Vilnius District. The paper is an attempt to conduct sociolinguistic research of the Polish population.